A linguistic analysis of old Irish hymns in the Liber Hymnorum - Doherty, James (Trinity College (Dublin, Ireland). Department of Irish and Celtic Studies, 2008)
The Liber Hymnorum (Book of Hymns) is a document containing hymns that were sung in early Irish monasteries in the seventh, eighth and ninth centuries. The Liber Hymnorum is preserved in two manuscripts: Trinity College Dublin’s catalogue T. 1441, dated to the late 11th century, and the Franciscan catalogue A2, dated to the early 12th century. The Trinity and Franciscan texts seem to be independent recensions of a lost exemplar, which is thought to have been written in the late tenth century. The majority of the hymns in the collection are composed in Hiberno-Latin, but there are seven hymns in the native vernacular from the Old Irish period (700-900AD). The hymns, both those in Latin and in Irish, are supported by Middle Irish prefaces, interlinear glosses and lengthy scholia written in the margins.
Keywords: Irish & Celtic Languages, Ph.D.; Ph.D. Trinity College Dublin